Interactive Edutainment Game: Learning Media for Integer Operations for Middle School Students - Aryanti, letty; Aryasandy, Nensy; Yerizon, Yerizon (JDIME: Journal of Development and Innovation in Mathematics Education, 2024)
This study aims to develop and evaluate the effectiveness of an HTML5-based interactive learning media in the form of an edutainment game to enhance Junior High School (JHS) students' understanding of integer arithmetic operations. Adopting a Research and Development (R&D) approach, the media was developed through seven stages of the Borg and Gall model: needs analysis, planning, product development, expert validation, initial product revision, field testing, and final product revision. The research subjects consisted of 30 seventh-grade students, one mathematics teacher, and three expert validators. The validation results indicated that the media was "highly valid" with average scores of 4.8 for content, 4.7 for visualization, 4.9 for interactivity, and 4.8 for technology functionality. The practicality of using the media received positive responses, with scores of 4.6 from the teacher and 4.7 from students, indicating comfort and ease of use. Pretest and posttest results showed a significant improvement in students' understanding, with an average pretest score of 55.3 and a posttest score of 82.1, reflecting a 48.5% improvement with a significance value (0.000 < 0.05), indicating a statistically significant difference in student learning outcomes before and after using the media. Therefore, this media is deemed suitable as an alternative innovative, interactive, and student-centered mathematics learning tool for 21st-century learners.